PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBENTUK VIDEO TUTORIAL BERBAHASA INGGRIS PADA PEMBELAJARAN FISIKA SISWA SMA - Yonaida Ikrayenti (Universitas Negeri Padang, 2013)
Abstract —– On physic learning in SMA teacher has to prepare instructional design of Physics include syllabus, lesson plan, learning material and evaluation instrument. This instructional design of Physics still in printed. One of innovation in learning is making an instructional design like tutorial video in English. The purposes of this research are to produce an instructional design like tutorial video in English that is valid, practice and effective on Physics learning. The design of this research is Research and Development (R&D) by using 4-D model. The procedures are Define, Design, Develop, and Disseminate. The developed designs are syllabus, lesson plan, handout, students’ worksheet, and evaluation. The instruments to collect the data are validity sheet from the experts, try-out practicality sheet from physics teachers, try-out practicality sheet from students, and test. Techniques of product analysis used are analysis of product validity, analysis of practicality, and analysis of effectiveness. The object of this research is the students of class XI IA 1 SMA N 3 Bukittinggi that consists of 27 students. There are three main result of this research. First, there is success to developing an instructional design of Physics that is valid in Physics learning. Second, the result of analyze data show that the instructional design of Physics that is practice in Physics learning based on teachers and students evaluation. Third, the result of analyze effectiveness show that the implementation of instructional design of Physics that is effective in Physics learning based on increasing of students aoutcome according to significant. Keywords —– instructional design of Physics, physics learning, tutorial video, tutorial video in English